Food for thought : service-learning research in Asia - Shumer, Robert, 1947-; Ma Hok-ka, Carol; Chan Wing Yee, Constance (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Service-learning researches have been growing and expanding around the world. While much of the early work was carried out in the US and Europe, such efforts have been developing in Asia for the past few decades. The use of the term, 'service-learning' was not popular, while use of community engagement, volunteerism, social services are more common among community practitioners and academics, with the rapid development of service-learning, both research and community-based programs have been growing throughout Asia over, the last decade. One of the major movements in that part of the world has been the Service-Learning Asia Network (started in 2005), where more than 11 countries have unified to share their efforts collectively through conferences and journals. In this new book we have examples from five (5) different places: China, Singapore, Hong Kong, Indonesia, and India. These models follow a recent publication of Asian research found in the Michigan Journal of Community Service Learning, published in Summer 2019 after the 7th Asia Pacific Regional Service-Learning conference in Singapore. The chapters represent some of the exciting work that is developing in Asia, highlighting the rich and powerful connections between universities and communities throughout the region. Excellent examples of various kinds of study, from case studies, to qualitative research, to mixed method designs are included. In addition, the focus of the studies, from student learning, community change, innovative practice, and institutional development and change are provided to illustrate the rich diversity of work occurring throughout Asia. The book is available in both English and Chinese"--